Characterization of nuclear factor of activated T-cells-c3 (NFATc3) and gene expression of upstream-downstream signaling molecules in response to immunostimulants in Pacific red snapper cells. (January 2018) - Angulo, Carlos; Alamillo, Erika; Ascencio, Felipe; Reyes-Becerril, Martha
Abstract: The nuclear factor of activated T cells (NFAT) proteins have crucial roles in the development and function of the immune system since they not only regulate activation of T cells but are also involved in the control of thymocyte development and T-cell differentiation. In this study, NFATc3 was characterized from the Pacific red snapper, Lutjanus peru . LpNFAtc3, which contains an open reading of 3300 bp frame coding for a protein of 1100 aa with a predicted molecular weight of 118.52 kDa. The predicted protein showed a conserved NFAT family structure with signature motifs and domains, sharing high identity (up to 76%) compared to other fish sequences. NFATc3 gene expression was analyzed by real time-PCR in head-kidney cells (leukocytes and lymphocytes) following yeast, zymosan and Vibrio parahaemolyticus stimulation along with the expression of upstream (ILF2, ILF3 and CaN) and downstream (CD3, TCRβ, IL-6 and IL-12) molecules. This study revealed a broad expression of NFATc3 with a relative strong expression in intestine and lymphocytes. The expression of NFATc3 was differentially up-regulated after stimulation with yeast in head-kidney leukocytes and after bacterial infection in lymphocytes at 24 h. Interestingly, the yeast and zymosan were able to activate ILF2, ILF3 and CaN mRNA gene expression in both kinds of cells. On the other hand, NFAT downstream genes such as CD3, TCRβ, IL-6 and IL-12 were significantly up-regulated in leukocytes stimulated with yeast or zymosan at 12 h; however in lymphocytes, this up-regulation was detected when cells reacted to V. parahaemolyticus stimuli at 24 h. Stimulating Pacific red snapper leukocytes with immunostimulants as yeast significantly up-regulated the expression of NFATc3, and up- and down-stream molecular genes and NFATc3 lymphocytes expression were potentially involved in responses to invasion of bacterial pathogens in an early immune response. Highlights: NFATc3 functional architecture from Lutjanus peru was characterized in silico . NFATc3 was highly expressed in intestine and isolated lymphocytes. NFATc3 was up-regulated in HK leukocytes (yeast) and lymphocytes (bacteria). Vibrio parahaemolyticus strongly activates NFAT downstream expression in lymphocytes. NFAT-related genes are differentially modulated by yeast and bacteria.